Three essays on gender wage differentials - Fang, Zheng (2012)
Gender wage gaps in favor of men have been widely documented across a large number of countries. Such gaps can be partially explained by differences in productivity related characteristics, such as education and experience between men and women; the part not explained by differences in characteristics is often referred to as potential discrimination in the labor market. The issue has been studied extensively in the literature, especially at the mean; however, distributional patterns may be of more interest as they relate to policy-making, when targeted intervention is deemed appropriate. This thesis consists of three self-contained essays which study the gender wage differentials and potential gender discrimination across the earnings distribution.